Hubungan Lama Penggunaan Kontrasepsi Suntik Depo Medroxy Progesteron Acetate (DMPA) Dengan Kadar Kolestrol Total Pada Akseptor KB - Veradilla; Mauluddina, Faulia; Saswita, Reni; Suryanti, Yuli (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2025)
Birth planning and readiness to overcome complications Depo Medroxy Progesterone Acetate (DMPA) injectable contraception is a popular hormonal contraceptive method among women. Its ease of use and effectiveness in preventing pregnancy make DMPA a popular choice. However, long-term use of DMPA has been associated with several side effects, one of which is an increase in total cholesterol levels. Cholesterol is an important fat substance for the body, but high cholesterol levels can increase the risk of cardiovascular diseases such as coronary heart disease and stroke. This type of research is analytical with a cross-sectional approach. This research method includes quantitative research. The purpose of this study is to determine the relationship between the duration of use of depo medroxy progesterone acetate (DMPA) injectable contraception and cholesterol levels in family planning acceptors. The population in this study were all DMPA injectable contraceptive acceptors who visited PMB Ferawati Palembang. The sample of this study was some of the DMPA injectable contraceptive acceptors who visited PMB Ferawati during the study. From the results of the Chi-Square test, the p value was obtained = 0.002 < α (0.05), this indicates that there is a significant relationship between the duration of using DMPA injectable contraception and cholesterol levels at PMB Ferawati Palembang in 2025